How to distinguish memory representations? A historical and critical journey - Marina Trakas (Voluntas, 2019)
Memory is not a unitary phenomenon. Even among the group of long-term individual memory representations (known in the literature as declarative memory) there seems to be a distinction between two kinds of memory: memory of personally experienced events (episodic memory) and memory of facts or knowledge about the world (semantic memory). Although this distinction seems very intuitive, it is not so clear in which characteristic or set of interrelated characteristics lies the difference. In this article, I present the different criteria proposed in the philosophical and scientific literature in order to account for this distinction: (1) the vehicle of representation; (2) the grammar of the verb “to remember”; (3) the cause of the memory; (4) the memory content; and (5) the phenomenology of memory representations. Whereas some criteria seem more plausible than others, I show that all of them are problematic and none of them really fulfill their aim. I then briefly outline a different criterion, the affective criterion, which seems a promising line of research to try to understand the grounds of this distinction.